Promotion Mix Studio Foto Dalam Meningkatkan Penjualan Jasa Foto - Rifki Ilham Widiawan; Wiki Angga Wiksana (UNISBA Press, 2022)
Abstract. This research was conducted with the aim of explaining and understanding the object specifically as a phenomenon of the newness of the data regarding the ZOOM Photography Promotion Mix which keeps this photo studio busy with visitors who want to capture its precious moments even in the midst of the current pandemic. With the Promotion Mix indicators studied, among others: advertising activities undertaken, personal selling activities undertaken, word of mouth promotion activities, promotional activities that have a major impact on increasing sales of photo services at the ZOOM Photography photo studio. The results of this study prove that the promotional mix activities that have been carried out by ZOOM Photography are able to increase sales of photo services. The results also show that promotional activities that have a major impact on increasing sales of ZOOM Photography photo services are advertising promotion activities supported by word of mouth promotion activities in the form of stories of satisfying experiences from ZOOM Photography consumers. Abstrak. Penelitian ini dilakukan bertujuan untuk menjelaskan dan memahami objek secara khusus sebagai suatu fenomena perihal kebaharuan data mengenai Promotion Mix ZOOM Photography yang membuat studio foto ini tetap ramai didatangi pengunjung yang ingin mengabadikan momen berharganya meski di tengah pandemi sekarang ini. Dengan indikator Promotion Mix yang diteliti, antara lain: kegiatan periklanan yang dilakukan, kegiatan personal selling yang dilakukan, kegiatan promosi word of mouth, kegiatan promosi yang memiliki dampak besar terhadap peningkatan penjualan jasa foto pada studio foto ZOOM Photography. Hasil penelitian ini membuktikan kegiatan promotion mix yang sudah dilakukan oleh ZOOM Photography mampu meningkatkan penjualan jasa fotonya. Hasil penelitian juga menunjukkan bahwa kegiatan promosi yang memiliki dampak besar terhadap peningkatan penjualan jasa foto ZOOM Photography yaitu kegiatan promosi periklanan yang didukung dengan kegiatan promosi word of mouth berupa cerita pengalaman yang memuaskan dari para konsumen ZOOM Photography.